Experimental study on the cavity evolution and liquid spurt of hydrodynamic ram - Anran Chen; Xiangdong Li; Lanwei Zhou; Yangziyi Ji (Defence Technology, 2022)
In research of the characteristics of the cavity evolution, the pressure, and the liquid spurt in hydrodynamic ram, the experiment of the high-velocity fragment impacting the water-filled container had been conducted. The relationships between the above three characteristics have been researched. The evolution of the cavity can be divided into three processes according to its shape characteristics. The first liquid spurt occurred in Process Ⅱ and the rest of it occurred in Process Ⅲ. The duration of the second liquid spurt is longer than the first liquid spurt. When the impact velocity of the fragment is less than 996 m/s, the velocity of the second liquid spurt is the highest. When the velocity of the fragment is greater than 996 m/s, the velocity of the first liquid spurt is the highest. The maximum velocities of the first and second liquid spurt are 111 m/s and 94 m/s respectively. The pressure fluctuated sharply in Processes Ⅰ and Ⅲ. The maximum peak pressures in the shock and the cavity oscillation phases are 15.51 MPa and 7.96 MPa respectively. The time interval of the two adjacent pressure pulses increases with the increase of the fragment velocity.